ANALISIS ELEMEN VISUAL KEMASAN CHIKI SNACK - Nico Yudha Prathama; Dodi Setianto (Universitas Trisakti, 2015)
Abstract‘The Visual Element Analysis of Chiki Snack Packaging’. Packaging designgraphic elements that differ between products allegedly have differentmarketing purposes. It is interesting authors to analyze graphical elements onthe packaging chiki. Analysis includes elements that differ in packaging design.Designed packaging there are several elements that influence consumers to takeaction that is expected by manufacturers such as color, shape, brand or logo,illustration, typography, and layout. With the election of good packaging designelements and according to the nature of the product can affect potentialcustomers in choosing what products they will buy. In this paper there is anexplanation of packaging design factors, and some examples of good packagingcriteria, and therefore I took the theme